Adult Autism Spectrum Disorders and its Psychiatric Comorbidities - Ramos, Jorge (2013)
Unlike in children, the autism spectrum disorders (ASD) in adults have not been so extensively studied, with consequent difficulties in diagnosis and management in adulthood, especially in the presence of psychiatric comorbidity. The authors have made a selective review of literature, focusing on ASD definition, its epidemiology, diagnosis and factors that may influence its outcome. The main psychiatric comorbidities in adults will also be focused, as well as its impact in the clinical presentation of psychiatric disorders. Despite the tendency for a progressive symptomatic improvement in adulthood, ASD affect patients during their whole life. Furthermore, it is estimated that they affect a considerable number of patients, making even more relevant a thorough knowledge of these pathologies.